2019
DOI: 10.1016/j.jallcom.2019.151795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zr on the high cycle fatigue and mechanical properties of Al–Si–Cu–Mg alloys at elevated temperatures

Abstract: The Zr-modified Al-Si-Cu-Mg alloy with 0.14wt%Zr addition was studied against the counterparts of commercially used EN-AC-42000 (Al7Si0.5Cu) baseline alloy for the effect of Zr on the high cycle fatigue (HCF) and mechanical properties at elevated temperatures of 150, 200, 250 o C. It was found that the fatigue life was significantly improved by 8-10 times at the high stress amplitude of 140 MPa in the Zr-modified alloy at all different temperatures. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 46 publications
(65 reference statements)
1
14
0
Order By: Relevance
“…However, its performance drops sharply at 300 °C due to the higher diffusion rate and solubility of Cu in the matrix at higher temperature. The morphological evolutions of the precipitates in the Al-Si alloy for both 300 °C and 350 °C exposure processes were reported by Liu et al [ 46 ] and Tian et al [ 16 ]. The precipitation was rarely changed after the precipitates rapidly coarsening during the first few hours of exposure process.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, its performance drops sharply at 300 °C due to the higher diffusion rate and solubility of Cu in the matrix at higher temperature. The morphological evolutions of the precipitates in the Al-Si alloy for both 300 °C and 350 °C exposure processes were reported by Liu et al [ 46 ] and Tian et al [ 16 ]. The precipitation was rarely changed after the precipitates rapidly coarsening during the first few hours of exposure process.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, the dispersoid can be regarded as Al 2 (Cu, Fe), which act as an important factor for improving the micro-hardness of the matrix in this condition. Similarly, some new dispersoids have also been reported at elevated temperature in the available references [16,46,49]. Sui et al found that the addition of Gd induces Al 3 CuGd dispersoid formation at grain boundaries, which can simultaneously improve the strength of the eutectic Al-Si alloy at both room and elevated temperature [49].…”
Section: The Effect Of Thermal Exposure On the Micro-hardness Of Al Mmentioning
confidence: 90%
“…The basic intermetallic phases consisted of α-Al dendrites (1#), Al-Si eutectic (2#), Al2Cu with granular and blocky-shapes (3#,4#), and Q-Al5Cu2Mg8Si6 (5#). By searching references and comparing, Al43.1Si22.5Cr (6#), Al18.5Si7.3Cr2.6V (7#), and Al7.9Si8.5Cr6.8V4.1Ti (8#) belong to the CrVTi rich phase [8][9][10][11][12]; Al10.7SiTi3.6 (9#), Al6.7Si1.2TiZr1.8 (10#), and Al21.4Si3.4Ti4.7VZr1.8 (11#) belong to TiVZr rich phase [11][12][13];…”
Section: Microstructural Analysismentioning
confidence: 99%
“…Al14.7Si2.2Mn4.5Fe (12#), Al38.2Si7Mn2.5Mo4.6Fe (13#), Al67.8Si8.3Mn5.2Fe3Mo1.1Cu (14#), Al74.1Si5.7Mn3.6Cr2.1Fe (15#), and Al86.3Si5.1Mn2.1Mo2.4Cr1.4Fe (16#) belong to the MoMnFe rich phase [9][10][11][12][13][14]; Al8.4Si24.1Ti2.3V3.3Mo10.7Cr (17#) and Al13Si50Ti5.9V8.4Cr6.1Mo13.8(18#) belong to the TiVMo rich phase [15]. 3.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…One attempt aimed to modify Al-Si alloys with heatresistant Al 3 X dispersoids and precipitates. Transition metals such as Sc, Zr, Ti, V, and Ni [4][5][6][7][8][9][10][11][12][13] were found to be effective. However, the volume fraction of Al 3 X phase obtained through precipitation is usually very low, and some of these elements are very expensive, thus limiting industrial applications of such materials.…”
Section: Introductionmentioning
confidence: 98%